Legal Reform of Legal Profession Amidst the Development of Artificial Intelligence in Indonesia: The Perspective of Mesu Budi's Philosophy of Law - Muh. Ali Masnun; Dicky Eko Prasetio; Denial Ikram; Puja Aqdamuyasyaro P (NOVUM : JURNAL HUKUM, 2025)
The use of Artificial Intelligence (AI) within the legal profession raises significant concerns about whether the extensive application of AI could potentially replace human roles in this field. This study aims to analyze the challenges and dynamics associated with the implementation of AI in the legal profession, and to compare AI regulations across Indonesia, Malaysia, and the European Union. This research is a normative legal study employing conceptual, case-based, and legislative approaches. The findings affirm that AI will not replace the role of humans in the legal profession. As an officium nobile, the legal profession inherently requires moral, humanitarian, and value-based considerations that can only be performed by humans. The presence of "mesu budi"—a concept reflecting comprehensive utilization of IQ, EQ, and SQ—underscores that these facets are uniquely human and cannot be substituted by AI. The comparative analysis of AI regulations between Indonesia, Malaysia, and the European Union reveals that Indonesia's regulatory framework is lagging and lacks specific provisions regarding the use of AI in the legal profession. This study recommends the establishment of dedicated regulations for AI, particularly concerning its application in legal professions and associated accountability measures.